Capacity Optimization of MISO System in Intercell Interference of Visible Light Communication System. (26th August 2022) - Ali, Agha Yasir; Abdelgader, Abdeldime M. S.; Farhi, Lubna; Laila, Umm E.; Wang, Shujun
Abstract : The capacity of multiple input and single out (MISO) system is investigated in intercell interference environment of a visible light communication (VLC) system. The interference is dominating in cell edges and the center of the room due to overlapping of light signals from neighbor cell. The footprint of one cell extends at high SNR, and consequently, this increases the intercell interference regions. Therefore, the channel capacity is greatly deteriorated due to interference power. In this paper, the channel capacity can be improved using diversity gain of MISO-based VLC system. The light-emitting diode (LEDs) of MISO system in a cell can use the same data to improve the diversity gain of the system. The MISO array is derived as per SNR requirements in interference region of the room. The capacity of the MISO system is examined and compared with that of the single input and single output (SISO). A trade-off of the MISO array is obtained at different SNRs to achieve the interference free capacity system. Theoretical and simulation capacity response show that the interference is considerably minimized by using diversity gain of MISO system. The interference free capacity is achieved at 44 dB, 49.5 dB, and 51.7 dB SNR using 4X1, 9X1 and 16X MISO system, respectively.